Linux on Azure : deploying and managing Linux on Azure (Addison-Wesley Professional, 2017)
"Deploying Linux on Azure LiveLessons is a unique video product that teaches you everything you need to know to get up and running with Linux if you are a Microsoft Professional who needs to deploy, manage, and monitor Linux in an Azure environment. This comprehensive video course starts with the essentials, and then quickly moves forward from there, focusing on tasks that are specific for managing Linux workloads in an Azure environment. Content includes managing containers, monitoring Linux, working with configuration management tools, and working with Azure-specific services for managing Linux. This is a must-see course for anyone who needs to learn how to administer Linux on Azure."--Resource description page